2018
DOI: 10.3102/0034654318779957
|View full text |Cite
|
Sign up to set email alerts
|

Developing a STEM Identity Among Young Women: A Social Identity Perspective

Abstract: We conducted a systematic review of empirical research focused on the experiences of female students in science, technology, engineering, and mathematics (STEM) during middle and high school. Drawing on social identity theory, recent research was synthesized to explore how aspects of the social environment influence STEM identity development. Findings indicate that young women experience challenges to their participation and inclusion when they are in STEM settings. Additionally, we found that perceptions rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
179
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(200 citation statements)
references
References 100 publications
(149 reference statements)
6
179
0
15
Order By: Relevance
“…A search for reviews of STEM education research found multiple reviews that could suggest approaches for identifying publications (e.g., Brown, 2012;Henderson, Beach, & Finkelstein, 2011;Kim, Sinatra, & Seyranian, 2018;Margot & Kettler, 2019;Minichiello, Hood, & Harkness, 2018;Mizell & Brown, 2016;Thibaut et al, 2018;Wu & Rau, 2019). The review conducted by Brown (2012) examined the research base of STEM education.…”
Section: Guidance From Prior Reviews Related To Stem Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…A search for reviews of STEM education research found multiple reviews that could suggest approaches for identifying publications (e.g., Brown, 2012;Henderson, Beach, & Finkelstein, 2011;Kim, Sinatra, & Seyranian, 2018;Margot & Kettler, 2019;Minichiello, Hood, & Harkness, 2018;Mizell & Brown, 2016;Thibaut et al, 2018;Wu & Rau, 2019). The review conducted by Brown (2012) examined the research base of STEM education.…”
Section: Guidance From Prior Reviews Related To Stem Educationmentioning
confidence: 99%
“…In contrast to reviews on STEM education, in general, other reviews focused on specific issues in STEM education (e.g., Henderson et al, 2011;Kim et al, 2018;Margot & Kettler, 2019;Minichiello et al, 2018;Schreffler, Vasquez III, Chini, & James, 2019;Thibaut et al, 2018;Wu & Rau, 2019). For example, the review by Henderson et al (2011) focused on instructional change in undergraduate STEM courses based on 191 conceptual and empirical journal articles published between 1995 and 2008.…”
Section: Guidance From Prior Reviews Related To Stem Educationmentioning
confidence: 99%
“…However, other research has suggested that social identity is multi-faceted, and includes a facet of typicality (referred to as self-stereotyping by Leach et al, 2008;Starr, 2018). This perspective recognizes that two elements are essential for developing a social identity: (1) seeing oneself as a member of the group, and (2) feeling that the members of the group accept you as a member (Kim et al, 2018). Although the first may be captured by the importance of a social group to one's self-concept, the latter may be better captured by the self-perception that you are a prototypical member of the group-that you possess the skills, knowledge, beliefs, practices, and principles of a member of that particular group (Ibarra, 1999;Nadelson et al, 2015).…”
Section: What Is Science Identity?mentioning
confidence: 99%
“…These studies seek to shed light on factors which may support identity development in middle school and high school students, in order to improve gender parity in STEM fields (e.g. [25], [26]). Buontempo, Riegle-Crumb and Patrick [25] investigated the factors which influence the gender differences in engineering identity in male and female high school students.…”
Section: Engineering Identity In Middle and High Schoolmentioning
confidence: 99%
“…They concluded that the primary factors are lower self-efficacy and interest in female students, though this could be mitigated by focusing on improving female students' attainment value, defined as the importance students put on engineering and engineering tasks relative to other fields, for the field of engineering. Kim, Sinatra and Seyranian [26] investigated the impacts of social factors, and concluded that in order to improve women's representation in STEM fields, it is necessary to both support female precollege students in their STEM identity development and to work to change the larger perception of who pursues a STEM degree. Both studies investigated the importance of relationships, including peer, family and mentor relationships, on female students' engineering identity, though they came to differing conclusion, as Kim et.…”
Section: Engineering Identity In Middle and High Schoolmentioning
confidence: 99%